Influência da ativação ultrassônica do ácido glicólico na resistência à fratura da dentina radicular – estudo in vitro - Brammer, Mariana Patussi (2022)
This study aimed to evaluate, in vitro, the influence of ultrasonic activation of glycolic acid on the fracture resistance of root dentin. Thirty-six extracted single-rooted bovine teeth were used in the present study. The coronal portion was sectioned from the roots using an Isomet 1000 precision cutter (Buehler, Illinois, United States) under constant refrigeration, so that straight roots measuring 15 mm in length were obtained. The samples were standardized and randomly divided into three groups (n=12) according to the final irrigation protocol: G1(control group) - distilled water (DW); G2 – 17% glycolic acid (GA) and G3 – 17% GA + ultrasonic activation (US). A compressive load was applied vertically to the coronal surfaces of the roots in a universal testing machine, with a loading speed of 1 mm/minute until fracture occurred. Statistical analysis of the data was performed using Tukey's post-hoc tests and one-way ANOVA with a significance level of 5%. Results showed that no statistically significant differences were observed between groups (P > 0.05). It is concluded that the use of ultrasonic activation on glycolic acid did not influence the fracture resistance of root dentin.